2017
DOI: 10.1038/s41598-017-00815-3
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Related Factors in the Frontal Lobe of Alzheimer’s Disease Patients and Importance of Body Mass Index

Abstract: Estrogens play a physiologically important role in the brain, but controversies exist regarding the association between Alzheimer’s disease (AD) and estrogens. Estrogen-related factors were comprehensively examined in frontal lobe tissues from autopsied AD patients, and compared with controls. Concentrations of estrogens, expression of estrogen receptors (ERs), and estrogen-metabolizing enzymes (EMEs) which are important for determining the peripheral estrogen concentrations, were examined using liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, lower endogenous estradiol levels compared with age-matched controls have been reported in women with actual or incipient Alzheimer’s disease (e.g., [ 66 ]). It is unclear at the present time whether or not lower peripheral levels are reflected in the central CNS concentrations of women who have Alzheimer’s [ 67 ] or whether replacement estrogens taken in the early postmenopause may help to protect against the accrual or progression of AD pathology [ 68 •, 69 , 70 ] in at-risk women.…”
Section: Discussionmentioning
confidence: 99%
“…However, lower endogenous estradiol levels compared with age-matched controls have been reported in women with actual or incipient Alzheimer’s disease (e.g., [ 66 ]). It is unclear at the present time whether or not lower peripheral levels are reflected in the central CNS concentrations of women who have Alzheimer’s [ 67 ] or whether replacement estrogens taken in the early postmenopause may help to protect against the accrual or progression of AD pathology [ 68 •, 69 , 70 ] in at-risk women.…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol has been shown to improve cognition by mediating synaptic plasticity and increasing dendritic spine density (37), while testosterone has been shown to improve cognition by stimulating microglial phagocytosis, inhibiting neuroinflammation, and reducing Aβ deposition (38). A recent study found a significantly positive association between estrogen level and BMI in AD patients (39). It is well known that BMI is positively correlated with serum estrogen levels in postmenopausal women because of the high abundance of aromatase in adipose tissue (40).…”
Section: The Association Between Body Composition and Admentioning
confidence: 99%
“…Physiologically, androgens and estrogens are present in the body, with various rates among organs or individuals. The serum estrogen/androgen ratio is highest in premenopausal women, but lowest in postmenopausal women whose serum estrogen concentration is much lower than in men [ 42 , 43 , 44 , 45 , 46 , 47 ]. Intra- or peri-tumoral estrogen production is important in ER- and/or PR-positive tumors; however, TNBC or ER- and PgR-negative tumors, where local estrogen production is less active, are directly affected by the serum hormonal status [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%